2019
DOI: 10.1002/cam4.2251
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on outcomes in hepatocellular carcinoma: Inferences from primary insurance

Abstract: Background To investigate the impact of insurance status on outcomes in patients with hepatocellular carcinoma (HCC). Methods Patients diagnosed with HCC in the cancer registry from 2005 to 2016 were retrospectively stratified by insurance group. Overall survival was assessed via Kaplan‐Meier curves and Cox proportional hazard models including potential confounders in multivariable analyses. Results Seven hundred and sixty‐nine patients met inclusion criteria (median age 63 years, 78.8% male, 65.9% Caucasian).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Enrollees in UEBMI always have a relatively higher SES and may pay close attention to health status, get more cancer screenings, and have full access to medical treatment. Additionally, some studies have also demonstrated that lower SES was associated with worse HCC-specific survival (30)(31)(32). Furthermore, previous studies examining the relationship between insurance and survival in other countries also have shown that patients with a good insurance status have better survival than those with poor insurance status, not only among HCC patients, but also among many other cancers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Enrollees in UEBMI always have a relatively higher SES and may pay close attention to health status, get more cancer screenings, and have full access to medical treatment. Additionally, some studies have also demonstrated that lower SES was associated with worse HCC-specific survival (30)(31)(32). Furthermore, previous studies examining the relationship between insurance and survival in other countries also have shown that patients with a good insurance status have better survival than those with poor insurance status, not only among HCC patients, but also among many other cancers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…15 A wide range of survival durations has been reported for HCC patients from liver transplant programs, 12 and from a mixture of hospitals with or without liver transplant programs on site. 6,13,16 Data on HCC outcomes ascertained from SEER database have limitations of under reporting treatment modalities like TACE or non-reporting of key indicators like HCC surveillance that are associated with early diagnosis and prognosis of HCC. 7 Nonetheless, compared to Adler et al's report and the 20-month survival of our cohort, a lower median survival rate of 18 vs 11 vs 8 months was reported for commercial, Medicaid and uninsured patients respectively from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing subgroups according to the initial treatment allocation, the highest mortality rates associated with the Medical Aid group was evident in the TACE group (fully adjusted HR, 2.40; 95% CI, 1.25 to 4.58), the other treatments group (fully adjusted HR, 2.86; 95% CI, 1.85 to 4.41), and the no treatment group (fully adjusted HR, 2.69; 95% CI, 1.79 to 4.04), but not in patients in the curative treatment group (fully adjusted HR, 1.68; 95% CI, 0.39 to 7.13). In a previous study, 10 the authors suggested that while patients with lower SES or less desirable insurance may present with more advanced liver disease or cancer, if they receive the appropriate treatment for their HCC stage and underlying liver disease, their insurance and perhaps even SES may not affect survival. However, in the current study, the lower SES groups showed a more severe impact on the mortality in patients with non-curative treatments.…”
Section: Discussionmentioning
confidence: 99%